Perancangan Game Edukasi Pengenalan Bagian Tubuh Manusia Dengan Bahasa Hubula-Indonesia - Hence Beedwel Lumentut; Gabriela Karen Tuuk; Yopi Meage (Jurnal Sintaks Logika, 2025)
Along with the development of information technology, various areas of life have undergone significant transformations, including in the education sector. The information technology use in the teaching and learning process has been proven to improve the quality of learning, especially in early childhood education. This research aims to develop a Rapid Application Development (RAD) educational game that introduces human body parts using Hubula and Indonesian, the local language used by the Wamena people. The prototype development method was used to create an early model of the game as an alternative interactive media that was more interesting than conventional book-based learning methods. This game is expected to increase students' interest and understanding of the anatomy of the human body in a more effective and fun way. In addition, using regional languages in learning media is also an effort to preserve local culture. With an interactive and innovative approach, this game prototype serves as a learning tool to introduce regional cultural values to the younger generation. The results of this development show the great potential of integrating technology and culture in improving the quality of education.